Studying the technology and medicinal properties of amaranth growth - Jumayeva Dinora (Zien Journals, 2023)
This article outlines the technology, biology, ecology, importance and chemical composition of amaranta growth in agriculture and agriculture. Although the name is unfamiliar to many, the treatment characteristics of the amaranth plant are known in medicine
Keywords: About amaranth veg; plant origin homeland; agrotechnology; chemical composition